Desain pembelajaran Etnomatematika pada materi perkalian dan pembagian siswa kelas III SD Negeri 72 Palembang - Dimas Hartawan; Nyiayu Fahriza Faudiah; Budi Utomo (IKIP Siliwangi, 2026)
This study aims to design and develop an ethnomathematics-based learning approach for multiplication and division topics for third-grade students at SD Negeri 72 Palembang using the Design-Based Research (DBR) methodology. The main issue addressed is students’ low understanding of multiplication and division concepts, which are often perceived as abstract. To overcome this, the learning design integrates local cultural elements, particularly the traditional marble game, as a concrete and familiar context for students. The study was conducted through three main phases: preparing for the experiment, design experiment (consisting of a pilot experiment and a teaching experiment), and retrospective analysis. The results show that the ethnomathematics approach through the marble game effectively enhances students’ understanding of multiplication and division concepts. Additionally, the study produces a relevant and applicable Local Instructional Theory (LIT) for implementing culturally contextualized mathematics learning